Prevalence of modifiable risk factors for non-communicable diseases in urban slum: a cross sectional study using WHO STEPS approach - Jain, Swati; Jain, Vikas; Jain, Swapnil; Jain, Shweta (International Journal Of Community Medicine And Public Health, 2019)
Background: Non communicable diseases (NCDs) represent a cluster of major chronic diseases. Smoking habit, alcoholism, low quality diet intakes, physical inactivity are some of the established risk factors of the NCDs. In developing country like India the problem of lifestyle and its consequent diseases needs to be addressed vigorously by all public health care personnel. Objective of the study was to assess prevalence of modifiable risk factors using the WHO STEPS approach in urban slum. Methods: A community based cross-sectional study was carried out in the field practice area of urban health training centre of the department of community medicine of PCMS and RC, Bhopal using questionnaire. Results: Highest prevalence of modifiable risk factor was inadequate diet (85.2%), followed by smokeless tobacco consumption (59.1%) and low physical activity (46.1%). Tobacco smoking (31.9%) and alcohol (22.6%) were next, followed by high blood pressure (20.1%). Prevalence of least risk factors was overweight (13.9%). Conclusions: It can be concluded from our study that the burden of risk factors for NCDs is quite high. Its prevalence even in the younger age groups is a pointer to the fact that the burden of NCDs is going to rise in near future.